2021
DOI: 10.1002/ppul.25628
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of laryngotracheoesophageal clefts and tracheoesophageal fistulae in children with dysphagia

Abstract: Laryngotracheoesophageal clefts (LTECs) and tracheoesophageal fistulae (TEF) are important structural causes of aspiration requiring bronchoscopy for diagnosis.Determining which children are at greatest risk for LTEC and TEF would enable clinicians to be more selective in performing bronchoscopy.Methods: Medical records of children aged 0-18 years who underwent flexible and rigid bronchoscopy for evaluation of dysphagia with aspiration were collected and analyzed to identify predictors of LTEC and TEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…While LTEC is rare, 1 in 10,000-20,000 live births (19), the incidence of LTEC is higher (7.6%-22%) in children with aerodigestive issues such as a chronic cough (20)(21)(22). Mattos et al (23) showed that 1 percent of surgically assessed aspirating patients had a TEF, and 26% had an LTEC. Full-term children with OPD and tracheal aspiration were 3 times more likely to have LTEC than children born prematurely who also aspirate.…”
Section: Otolaryngology Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…While LTEC is rare, 1 in 10,000-20,000 live births (19), the incidence of LTEC is higher (7.6%-22%) in children with aerodigestive issues such as a chronic cough (20)(21)(22). Mattos et al (23) showed that 1 percent of surgically assessed aspirating patients had a TEF, and 26% had an LTEC. Full-term children with OPD and tracheal aspiration were 3 times more likely to have LTEC than children born prematurely who also aspirate.…”
Section: Otolaryngology Perspectivementioning
confidence: 99%
“…Full‐term children with OPD and tracheal aspiration were 3 times more likely to have LTEC than children born prematurely who also aspirate. While OPD in preterm children is more likely to be functional than structural, LTEC was identified in 10% of them and must be considered (23). These data support the role of bronchoscopy in children with OPD with tracheal aspiration.…”
Section: Diagnostics Approaches To Opdmentioning
confidence: 99%
“…Although suspected aspiration is a recognized indication for flexible bronchoscopy (FB) and bronchoalveolar lavage (BAL) in children, 2,3 there is considerable variability among diagnostic practices (including the exact role of FB) in these individuals. In children with unexplained oropharyngeal dysphagia at risk for aspiration, combined airway endoscopy, consisting of both FB and direct laryngoscopy and rigid bronchoscopy (DLB), is often performed to assess lower airway health and evaluate for anatomical causes of aspiration such as laryngotracheoesophageal clefts (LTEC) and tracheoesophageal fistulas (TEF) 4–6 . Prior work has characterized actionable DLB findings in children with dysphagia 7,8 ; however, similar research is lacking with regard to FB.…”
Section: Introductionmentioning
confidence: 99%
“…In children with unexplained oropharyngeal dysphagia at risk for aspiration, combined airway endoscopy, consisting of both FB and direct laryngoscopy and rigid bronchoscopy (DLB), is often performed to assess lower airway health and evaluate for anatomical causes of aspiration such as laryngotracheoesophageal clefts (LTEC) and tracheoesophageal fistulas (TEF). [4][5][6] Prior work has characterized actionable DLB findings in children with dysphagia 7,8 ; however, similar research is lacking with regard to FB. Put another way, in children undergoing combined airway endoscopy for dysphagia, when a major focus is anatomical laryngeal evaluation achieved through DLB, the clinical contribution imparted through FB has yet to be established.…”
mentioning
confidence: 99%